The interaction between cancer and COVID-19: Risk factors and targeted interventions - Lucian da Silva Viana; Alython Araujo Chung Filho; Gina Torres Rego Monteiro; Andrea Sobral (PLoS ONE, 2025)
Background Cancer patients are particularly fragile, and hospitalization represents a significant additional risk for complications and death, especially given the vulnerability of this group during the global pandemic. The study objective entails analyzing the factors associated with severity and death of cancer patients diagnosed with COVID-19 hospitalized between 2020 and 2022, in the city of Rio de Janeiro, Brazil. Materials and Methods This is a cross-sectional study, with hospitalized patients with both diagnoses, cancer and COVID-19, through two national databases. Bivariate and multivariate regression analyses were performed, followed by an interaction analysis between the variables of interest in the multivariate regression. Findings A total of 1,336 cases were analyzed. Have comorbidity and hematological neoplasms were associated with mechanical ventilation (OR =  1.62 and OR =  2.14, respectively) and with ICU admission (OR =  1.44 and OR =  2.25, respectively). The age group of 60 years or older (OR =  1.33), have multimorbidity (OR =  1.38), and use mechanic ventilation (OR =  2.39) were associated with a higher risk of death from COVID-19. The multimorbidity had a synergistic effect with hospitalization before vaccination (AP =  0.29; 95%CI =  0.01 – 0.58) and the use of mechanical ventilation (AP =  0.54; 95%CI =  0.18 – 0.98). Interpretation These findings are crucial to guide clinical decisions, improve the management of care for these patients, and optimize the use of health resources in the epidemiological context imposed by the pandemic.